BioRowTel® data acquisition system
Presesntation of BioRowTel®, "the system, which can measure everything in rowing". According to the authors BioRowTel® is "the most flexible, accurate, can measure more variables in as a standard (e.g. vertical oar angle, segments velocities) and opened to any new transducers. It allows to collect data through up to 128 channels at 25, 50 and 100Hz with 14 bit resolution. ... BioRowTel® is an ideal solution for elite rowers in National teams and researchers in universities".